Jurisdiction in the territorial hierarchical administration office - Holcman, Borut (Lex localis, 2009)
Division of administrative powers is the result of concrete decisions made by the supreme power holders (ius eminens) to be present in the daily life an individual. Quarters, district offices (in Slovene: "kresije" p.l), counting offices, recruitment districts, and discrit boards were those agents of power that where used by the supreme power holder to ensure the common good through them. The holder's power originated from the supreme power holder. It was restricted by the degree at which he operated. According to the of things, the power was subordinated by the delegated competences, and they functioned on the principle of subsidiarity, or it was autonomous under control in the case of the Church. Pragmatism of each supreme power holder is reflected in observing the divisions in operation. They most frequently emerged from the controlled autonomy.
Keywords: birokracija; pravosodni sistemi; Štajerska; uprava; zgodovina